2023
DOI: 10.1039/d3dt01078c
|View full text |Cite
|
Sign up to set email alerts
|

The enhanced sensing properties of MOS-based resistive gas sensors by Au functionalization: a review

Sen Luan,
Jinhu Hu,
Mingliang Ma
et al.

Abstract: Au-functionalized MOS-based gas sensing materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 201 publications
0
8
0
Order By: Relevance
“…Actually, Au NPs can accelerate the dissociation of aromatic rings. 4,15 In addition, it can be observed that an excessive coating on the active surface of the CuFe 2 O 4 NTs, resulting from overloading Au NPs, leads to a decrease in xylene responses from the 3 and 5 wt % Au-CuFe 2 O 4 sensors, thereby reducing their utilization rate and overall catalytic activity. ■ AUTHOR INFORMATION…”
Section: Synthesis Of Au-cufe 2 O 4 Ntsmentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, Au NPs can accelerate the dissociation of aromatic rings. 4,15 In addition, it can be observed that an excessive coating on the active surface of the CuFe 2 O 4 NTs, resulting from overloading Au NPs, leads to a decrease in xylene responses from the 3 and 5 wt % Au-CuFe 2 O 4 sensors, thereby reducing their utilization rate and overall catalytic activity. ■ AUTHOR INFORMATION…”
Section: Synthesis Of Au-cufe 2 O 4 Ntsmentioning
confidence: 99%
“…10−14 Among these strategies, the utilization of Au nanoparticles (NPs) has proven effective in accelerating the dissociation of aromatic rings due to their remarkable catalytic activity. 15 For instance, Sui et al reported that Au-loaded MoO 3 hollow spheres showed enhanced performance in detecting BTX gases due to the synergistic effects of "spillover effect" (or chemical sensitization) and catalysis activity of Au NPs and Au/MoO 3 Schottky barrier. 10 Similarly, Li et al synthesized Au-loaded WO 3 •H 2 O nanocubes for improving the sensitivity and selectivity in xylene sensing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…67 Semiconductor materials are employed in these sensors as their sensing components. 68–71 The target gas molecules are drawn to the active spots on the semiconductor material when it comes in contact with it. Resistance changes as a result of this contact, which alters how electrons travel within the material.…”
Section: Sensitive Mechanisms Of Resistive Gas Sensorsmentioning
confidence: 99%
“…Redox reactions between the target gas and chemisorbed oxygen species are the mechanism of sensing . Fabrication of nanostructured MOS materials with a high specific surface area has proved to be an effective strategy to promote gas adsorption for enhanced sensing performance. , Alternatively, noble metal particles (such as Pt, , Pd, Rh, and Au) are extensively utilized as catalysts to optimize the sensing performance of MOS sensors due to their remarkable electronic and catalytic activity. Noble metal industrial applications in chemical sensors are, however, severely limited by their high cost.…”
mentioning
confidence: 99%